Understanding the link between gut microbiota, dietary intake, and nutritional status in children with autism and typical development - Mendive Dubourdieu, Paula; Guerendiain, Marcela (Frontiers in Nutrition, 2023)
Background Gut microbiota plays a potential role in human health and different disorders such as autism spectrum disorder (ASD). Therefore, we analyzed gut bacteria composition in children with ASD and typical development (TD), and its relationship with nutritional status and dietary intake. Methods A descriptive cross-sectional study was carried out in 3- to 12-year-old children (ASD = 30, TD = 28). Dietary intake (applying food frequency questionnaires) and body mass index-for-age (expressed in z-score) were determined. Children were divided into normal weight and excess weight (risk of overweight + overweight + obesity), and the ASD group was categorized into gluten- and casein-free diet (ASD-diet) or no diet (ASD-no diet). The relative abundance of gut bacteria was analyzed in fecal samples by 16S rRNA sequencing. Results Children with excess weight had lower Roseburia than normal weight. Fewer Bifidobacterium longum and higher Clostridium glycolicum were found in the ASD group compared with TD one. Participants with excess weight and ASD had lower Roseburia and Faecalibacterium prausnitzii and higher Eubacterium ventricosum and Flavonifractor plautii than the TD group with the same nutritional status. Positive and negative associations were found between the bacteria genus and species, and the intake of dairy, vegetable drinks, cereals with and without gluten, food source of proteins, fish, food source of fat, and coconut oil, in unadjusted models and after adjustment for age, diet/no diet, ASD/TD. Conclusion Significant differences in microbial community composition were found between children with ASD and TD, considering their nutritional status and dietary intake.